Dynamically Broken Symmetry in Periodically Gated Quantum Dots: Charge Accumulation and DC-current - Kwapiński, T.; Kohler, S.; Hänggi, P. (Відділення фізики і астрономії НАН України, 2010)
Time-dependent electron transport through a quantum dot and double quantum dot systems in the presence of polychromatic external periodic quantum dot energy-level modulations is studied within the time evolution operator method for a tight-binding Hamiltonian. Analytical relations for the dc-current flowing through the system and the charge accumulated on a quantum dot are obtained for the zero-temperature limit. It is shown that, in the presence of periodic perturbations, the sideband peaks of the transmission are related to the combination of frequencies of the applied modulations. For a double quantum dot system under the influence of polychromatic perturbations, the quantum pump effect is studied in the absence of a source (drain) and static bias voltages. In the presence of a spatial symmetry, the charge is pumped through the system due to a broken generalized parity symmetry. Дослiджено залежний вiд часу транспорт електронiв через квантову точку i систему двох квантових точок при зовнiшнiй полiхромнiй перiодичнiй модуляцiї рiвнiв енергiї в межах методу оператора часової еволюцiї з гамiльтонiаном сильного зв’язку. Одержано аналiтичнi формули для постiйного струму через систему та для заряду, який накопичено на квантовiй точцi у границi нульової температури. Показано, що в присутностi перiодичних збурень боковi максимуми передачi залежать вiд спiввiдношення зовнiшнiх модуляцiй. Вивчено ефект квантової накачки за вiдсутностi джерела (стока) i статичних напружень змiщення. У випадку просторової симетрiї заряд накачується через систему внаслiдок порушення симетрiї узагальненої парностi.